Symmetry axioms and perceived ambiguity - Peter Klibanoff; Sujoy Mukerji; Kyoungwon Seo (Queen Mary University of London, School of Economics and Finance, 2017)
Since at least de Finetti [7], preference symmetry assumptions have played an important role in models of decision making under uncertainty. In the current paper, we explore (1) the relationship between the symmetry assumption of Klibanoff, Mukerji and Seo (KMS) [21] and alternative symmetry assumptions in the literature, and (2) assuming symmetry, the relationship between the set of relevant measures, shown by KMS [21] to reflect only perceived ambiguity, and the set of measures (which we will refer to as the Bewley set) developed by Ghirardato, Maccheroni and Marinacci [14], Nehring [24, 25] and Ghirardato and Siniscalchi [15, 16]. This Bewley set is the main alternative offered in the literature as possibly representing perceived ambiguity. Regarding symmetry assumptions, we show that, under relatively mild conditions, a variety of preference symmetry conditions from the literature (including that in KMS [21]) are equivalent. In KMS [21], we showed that, under symmetry, the Bewley set and the set of relevant measures are not always the same. Here, we establish a preference condition, No Half Measures, that is necessary and sufficient for the two to be same under symmetry. This condition is rather stringent. Only when it is satisfied may the Bewley set be interpreted as reflecting only perceived ambiguity and not also taste aspects such as ambiguity aversion.
Keywords: D01; D80; D81; D83; 330; Symmetry; beliefs; ambiguity; ambiguity aversion; model uncertainty; Ellsberg